Oracle initialization parameters : pocket reference - Kreines, David C. (O'Reilly, 2004)
Oracle designed its database products to be flexible and configurable so they would operate on a variety of hardware platforms, and they succeeded--Oracle software runs on more than seventy computer platforms, from mainframes to PC networks to handheld PDAs. The secret to this flexibility lies in the software's initialization parameters, whose numerous settings can be configured for top performance in countless environments. On the downside, however, improper settings can slow a system down; even grind it to a halt. And with so many parameters--which change from version to version of Oracle s.